A mechanistic approach for in‐vitro anticancer activity via nucleic acid fragmentation by copper(II) complex anchored on MCM‐41. (6th January 2022) - Karim, Suhana; Dasgupta, Sanchari; Parveen, Rumana; Biswas, Subhendu; Das, Debasis
Abstract : Three new mononuclear copper Schiff base complexes, namely, ([Cu(L1)Cl].CH3 CN (HmC_1 ), [Cu(L2)Cl].CH3 CN (HmC_2 ) and [Cu(L3)Cl].CH3 CN (HmC_3 ) derived from ONO donor tridentate ligands HL1, HL2 and HL3, respectively, have been synthesized to check their efficacy as target‐specific next‐generation anticancer therapeutics. All the HmC s have been characterized by using various physicochemical techniques (i.e., single‐crystal X‐ray analysis, Fourier transform infrared [FT‐IR] spectroscopy and elemental analysis). Among the synthesized Schiff base complexes, HmC_3 was turned out to be most effective in killing cancer cell carried out on cultured human breast cancer cell line (MDA‐MB‐231) and human lung carcinoma cell line (A549). Finally, in order to improve the cellular permeability, particle size of HmC_3 was scaling down to nano‐regime by immobilizing it onto a suitable matrix MCM‐41@APTES (MCM‐41  = Mobil Composition of Matter No. 41 and APTES  = 3‐aminopropyltriethoxysilane) to generate MCM‐41@APTES@HmC_3 (MCM‐41@APTES@HmC_3  = HtC_3 ). Field‐emission scanning electron microscope (FESEM) and dynamic light scattering (DLS) study revealed the particle size of the synthesized HtC_3 nano‐composite was within nano‐regime and therefore could be further effective for biomedical applications. Furthermore, HtC_3 displayed better cancer cell killing property. To get insight into the mechanism of action of HtC_3, Annexin V‐FITC/PI analysis and TUNEL assay revealed that DNA damage phenomenon is accompanied with changes in cellular morphology leading to cell apoptosis. Cell migration assay on MDA‐MB‐231 cell with HtC_3 exposed the effectiveness of HtC_3 in arresting cancer cell migration. Therefore, all the in‐vitro studies demonstrated that the immobilization of the copper Schiff base complex onto a suitable matrix increased its efficiency and becomes a promising anticancer nano‐therapeutic agent. Abstract : A series of novel HmC is grafted on mesoporous silica containing nano‐carrier in a convenient way to scale down their size to nano‐regime as HtC for successful cellular uptake. These heterogeneous nano‐composite materials have been exploited as promising therapeutic agents.